Enhancing IPv6 enabled IoT system security using addressless architecture - Ashmita Tiwari; Chitran Pokhrel; Babu R. Dawadi (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
The growth and sensitivity of internet of things (IoT) deployments demand robust and efficient security mechanisms, especially at the addressing layer. Traditional IPv6 addressing is susceptible to scanning, spoofing, and tracking, especially in IPv6 over low-power wireless personal area networks (6LoWPAN) networks. This paper proposes a dynamic elliptic curve cryptography (ECC)-based IPv6 address generation mechanism for 6LoWPAN IoT networks. Encrypting Interface IDs (IIDs) while keeping the network prefix the same to improve security against scanning, inference, and correlation attacks. High entropy of 0.9836 and cryptanalysis confirm higher randomness and high resistance to wide vectors of attacks. Having computed an average delay of encryption as 2.5728 ms, the process ensures low latency and insignificant overhead. It is more secure and efficient than existing techniques and hence is ideal for real-time resource- constrained IoT applications.